New Homologues Series of Heterocyclic Schiff Base Ester: Synthesis and Characterization - Chong, Y.T.; Sarih, N.M.; Ha, S.T.; Sheikh, M.R.K. (Hindawi Publishing Corporation, 2016)
A homologous series of liquid crystal bearing with heterocyclic thiophene Schiff base ester with alkanoyloxy chain (CH3(CH2)nCOO–, where , 6, 8, 10, 12, 14, 16) was successfully synthesized through the modification of some reported methods. The structural information of these compounds was isolated and characterized through some spectroscopic techniques, such as FTIR, 1H, and 13C NMR and elemental analysis. Textural observation was carried out using a polarizing optical microscope (POM) over heating and cooling cycles. It was found that all synthesized compounds (3a–g) exhibited an enantiotropic nematic phase upon the heating and cooling cycle with high thermal stability. Moreover, a characteristic bar transition texture was observed for compounds 3f and 3g which have shown transition of nematic-to-smectic C phase. This has been further confirmed by obtaining relative phase transition temperature using the differential scanning calorimetry (DSC).